PENINGKATAN KETERAMPILAN TEKNOLOGI INFORMASI BAGI SISWA AKUNTANSI DALAM PENYUSUNAN LAPORAN KEUANGAN BERBASIS DIGITAL DI SMK MULTIMEDIA MANDIRI - Rizki, Sestri Novia; Jaya , Eko Amri; Fitrianto , Adi; Nasution , Vani Maharani; Rusdin , Febi Ramadhani; Ayu , Ilmi Sila; Hutagalung , Carli Apriansyah; Yusran , Rio Rahmat; Karnadi , Very (ASOSIASI IDEBAHASA KEPRI, 2025)
Community service activities at SMK Multimedia Mandiri aim to improve information technology skills for students majoring in Accounting in preparing digital-based financial reports. In today's digital era, the ability to use software such as Microsoft Excel and Google Spreadsheets is an important skill that must be possessed by prospective workers in the accounting field. This activity was carried out at SMK [School Name] and involved students of grades XI and XII majoring in Accounting as participants. The implementation method was in the form of interactive training, demonstrations, and direct practice in preparing digital financial reports including general journals, ledgers, trial balances, and profit and loss reports. The results of the activity showed an increase in participants' understanding and skills in operating spreadsheet applications and preparing financial reports efficiently and systematically. This service is expected to support students' readiness in facing the needs of the world of work that demands mastery of information technology in accounting practices.